2019
DOI: 10.5089/9781498303569.001
|View full text |Cite
|
Sign up to set email alerts
|

Financial Deepening, Terms of Trade Shocks, and Growth Volatility in Low-Income Countries

Abstract: This paper contributes to the literature by looking at the possible relevance of the structure of the financial system-whether financial intermediation is performed through banks or markets-for macroeconomic volatility, against the backdrop of increased policy attention on strengthening growth resilience. With low-income countries (LICs) being the most vulnerable to large and frequent terms of trade shocks, the paper focuses on a sample of 38 LICs over the period 1978-2012 and finds that banking sector develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 41 publications
(50 reference statements)
4
28
0
Order By: Relevance
“…In this respect, we hypothesise to find a negative effect on volatility. Dabla-Norris and Srivisal 2013and Kpodar et al (2019) found volatility-dampening effects for the corresponding indicator.…”
Section: Methodology and Datamentioning
confidence: 96%
See 3 more Smart Citations
“…In this respect, we hypothesise to find a negative effect on volatility. Dabla-Norris and Srivisal 2013and Kpodar et al (2019) found volatility-dampening effects for the corresponding indicator.…”
Section: Methodology and Datamentioning
confidence: 96%
“…The results for real GDP per capita, gross fixed-capital formation and private final consumption are consistent with those already presented in Section 4. Kpodar and Imam (2016) and Kpodar et al (2019) introduced an alternative approach to measure economic volatility. Their approach relied on the assumption that the long-term component of the real GDP per capita follows an AR (1)-process with a time-trend.…”
Section: Alternative Volatility Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature has now well established that the proneness of developing countries to shocks 2 , and the subsequent size and frequency of these shocks (e.g., Aguiar and Gopinath, 2007;Cariolle et al 2016;Guillaumont, 2009;Goujon and Guillaumont, 2016;Essers, 2013) reduce their economic growth (e.g., Almansour et al, 2015;Azomahou et al, 2015;Bacha, 1986;Blecker, 2009;Dabla-Norris and Gündüz, 2014;Guillaumont and Wagner, 2012) and contribute to strong fluctuations of economic growth (e.g., Barrot et al 2018;Kim et al, 2020;Letendre and Obaid, 2020;Kose and Riezman, 2001;Kpodar et al, 2018;Raddatz, 2007;Rasaki and Malikane, 2015).…”
Section: Introductionmentioning
confidence: 99%